2006
DOI: 10.1044/1092-4388(2006/056)
|View full text |Cite
|
Sign up to set email alerts
|

Mean Length of Utterance in Children With Specific Language Impairment and in Younger Control Children Shows Concurrent Validity and Stable and Parallel Growth Trajectories

Abstract: Purpose Although mean length of utterance (MLU) is a useful benchmark in studies of children with specific language impairment (SLI), some empirical and interpretive issues are unresolved. The authors report on 2 studies examining, respectively, the concurrent validity and temporal stability of MLU equivalency between children with SLI and typically developing children. Method Study 1 used 124 archival conversational samples consisting of 39 children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
130
4
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(161 citation statements)
references
References 37 publications
(41 reference statements)
17
130
4
10
Order By: Relevance
“…Although evidence regarding the reliability of productive language-sample measures has been mixed, especially from shorter samples (e.g., Gavin & Giles, 1996;Tilstra & McMaster, 2007), such measures have been associated with evidence of validity through developmental change with age up through age 13 years (Miller et al, 2005;Miller, Freiberg, Holland, & Reeves, 1992; M. L. Rice, Redmond, & Hoffman, 2006); correlation with other measures of linguistic complexity (DeThorne et al, 2008;Nippold, 2009;Nippold et al, 2014; M. L. Rice et al, 2006;Ukrainetz & Blomquist, 2002); and differentiation of clinical groups (e.g., Condouris, Meyer, & Tager-Flusberg, 2003;Scott & Windsor, 2000;Watkins, Kelly, Harbers, & Hollis, 1995).…”
Section: Mlumentioning
confidence: 99%
“…Although evidence regarding the reliability of productive language-sample measures has been mixed, especially from shorter samples (e.g., Gavin & Giles, 1996;Tilstra & McMaster, 2007), such measures have been associated with evidence of validity through developmental change with age up through age 13 years (Miller et al, 2005;Miller, Freiberg, Holland, & Reeves, 1992; M. L. Rice, Redmond, & Hoffman, 2006); correlation with other measures of linguistic complexity (DeThorne et al, 2008;Nippold, 2009;Nippold et al, 2014; M. L. Rice et al, 2006;Ukrainetz & Blomquist, 2002); and differentiation of clinical groups (e.g., Condouris, Meyer, & Tager-Flusberg, 2003;Scott & Windsor, 2000;Watkins, Kelly, Harbers, & Hollis, 1995).…”
Section: Mlumentioning
confidence: 99%
“…These results are in agreement with other authors [25][26][27] , who observed a strong influence of this variable in such a way that children who came from higher sociocultural environments showed more complex oral productions and a more advanced linguistic development than children from lower sociocultural backgrounds. However, other authors have not observed a correlation with the background of the children as Rice and colleagues 5 . These differences in the studies and their results may depend upon different variables, such as the age ranges analysed in each study, the kind of linguistic analysis undertaken and also the measures of sociocultural background (parents' level of education, family income and/or father's occupation,…).…”
Section: (Talc) This Test Encompasses Comprehensionmentioning
confidence: 87%
“…Despite the advantages of using samples of spontaneous discourse over formal tests, there are limitations, namely the way in which the collection process unfolds or the number of utterances that are collected and analysed 5 . Given these difficulties some authors have worked towards optimizing this process by proposing several strategies.…”
Section: Conflict Of Interest: Non-existentmentioning
confidence: 99%
“…First, this study provides initial evidence that for some preschoolers with severe speech impairments, modifications can be made to traditional language sampling analysis to yield useful linguistic measures, such as MLUw and percentage comprehensibility, even when exact word agreement cannot be achieved. Once these methodologies are further validated, including children with severe speech impairments in studies of children with language impairments -who typically are excluded from such investigations (e.g., Rice et al, 2006Rice et al, , 2010-may be possible. Second, comprehensibility from the language samples was correlated with single word comprehensibility from the I-ASCC, indicating that both approaches measured a similar construct for these participants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in studies focusing on children with language impairment, children with limited intelligibility are often excluded (e.g., Rice, Redmond, & Hoffman, 2006;Rice, Smolik, Rytting, & Blossom, 2010), despite the fact that speech impairment often co-occurs with language impairment. This practice is understandable, as collecting reliable and valid expressive language information for children with severe speech impairments presents significant challenges; spoken language is necessarily mediated by the presence of the speech impairment.…”
mentioning
confidence: 99%